2018
DOI: 10.3389/fmed.2018.00213
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Genetic Polymorphism Towards Pulmonary Tuberculosis Susceptibility

Abstract: Tuberculosis (TB) is still remains the major threat for human health worldwide. Several case-control, candidate-gene, family studies and genome-wide association studies (GWAS) suggested the association of host genetic factors to TB susceptibility or resistance in various ethnic populations. Moreover, these factors modulate the host immune responses to tuberculosis. Studies have reported genetic markers to predict TB development in human leukocyte antigen (HLA) and non-HLA genes like killer immunoglobulin-like … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(42 citation statements)
references
References 199 publications
0
40
0
2
Order By: Relevance
“…Clinical studies 12,[50][51][52] have shown that MTB-specific TNF-α response can discriminate latent and active disease state of tuberculosis. It has been reported that dysregulation of TNF-α due to genetic variation 53,54 can increase susceptibility to mycobacterial infection. Tobin et al 53 showed that even TNF-α mediates inflammatory responses to TB, excess production of TNF-α leads to necrosis of macrophage, resulting in extracellular mycobacterial growth that accounts for the worse outcome in TBM.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies 12,[50][51][52] have shown that MTB-specific TNF-α response can discriminate latent and active disease state of tuberculosis. It has been reported that dysregulation of TNF-α due to genetic variation 53,54 can increase susceptibility to mycobacterial infection. Tobin et al 53 showed that even TNF-α mediates inflammatory responses to TB, excess production of TNF-α leads to necrosis of macrophage, resulting in extracellular mycobacterial growth that accounts for the worse outcome in TBM.…”
Section: Discussionmentioning
confidence: 99%
“…On the other side, the study of TB susceptibility, has shed light onto various components of immunity to mycobacteria in humans. Different genetic polymorphisms which modulate the host immune response in favor of TB infection and disease progression have been identified in human leukocyte antigens (HLA), toll like receptors (TLR), vitamin D receptors (VDR), cytokines with their receptors and many other functional immune components (10, 11). Moreover, mendelian susceptibilities to mycobacterial disease (MSMD) have been identified as clinical conditions with selective susceptibility to poorly virulent mycobacteria in the absence of patent immunodeficiency (12).…”
Section: Host and Bacterial Determinants In Human Tuberculosismentioning
confidence: 99%
“…A relation may occur when the polymorphism itself is functional and leads to altered susceptibility to the disease, or when an allele SNP is in LDS with an allele which is associate with disease susceptibility, or because of a conflicting effect induced by population. Genetic markers in human leukocyte antigen (HLA) and non-HLA genes such as toll-like receptors (TLRs), cytokine/chemokines and their receptors and vitamin D receptor (VDR) have been documented in studies to predict TB susceptibility [ 22 ]. In fact, several studies have shown that genetic variations in cytokines/chemokines genes are associated with susceptibility to as TB as IFN-γ [ 23 ], IL-12 [ 24 ], IL-10 [ 25 ], and others [ 26 ].…”
Section: Discussionmentioning
confidence: 99%